Pharmacotechnological Studies of the Biomass of Chlorella vulgaris C-2019 as a Promising Source of Antibacterial Substances - A. V. Mitishev; E. E. Kurdyukov; E. F. Semenova; T. M. Fadeeva; I. Ya. Moiseeva; Ya. P. Moiseev (Разработка и регистрация лекарственных средств, 2022)
Introduction. Currently, research is being actively conducted to find new biological objects as sources of biologically active substances. This is necessary in order to obtain producers who will be profitable in cultivating, maintaining their vital activity and obtaining at the output a sufficient number and high quality of the target products. Micro-and macroalgae can be one of these sources.Aim. The aim of this study is to conduct a phytochemical analysis to confirm the presence of a wide range of BAC, as well as studies on the selection of optimal parameters for extracting chlorella C-2019 biomass in order to obtain extracts with a high content of BAC that have an antibacterial effect (pigments, flavonoids).Materials and methods. The object of the study was the biomass of the strain Chlorella vulgaris Beyerinck IPPAS C-2019. The fractional composition, humidity, ash content, and extractive substances were determined according to GF XIV, 2018. The work uses spectrophotometric, GLC methods, as well as the method of drip electrophoresis.Results and discussions. As a result of phytochemical analysis, the main BAC of chlorella biomass of strain C-2019 were determined. The presence of proteins (64 %), fatty acids (7 %), phenolic compounds (1.56 %), pigments (2.46 %), macro – microelements has been proven. The optimal raw material-extractant ratio is 1 : 50. Increasing the temperature and duration of extraction increased the yield of the main BAС.Conclusion. The phytochemical composition of promising plant raw materials is determined. The optimal conditions for the extraction of chlorella biomass in the preparation of the extract are established: the ratio of raw materials:extractant 1 : 50, extractant ethyl alcohol 95 %, extraction temperature 60–80 °C, triple extraction for 60, 60, 60 minutes.